Triple P with Sang Kancil: pronunciation, phonetics, and playbook / Nur Erysha Mohd Salam and Nor Afifa Nordin - Mohd Salam, Nur Erysha; Nordin, Nor Afifa (Academy of Language Studies, 2023)
‘Triple P with Sang Kancil: Pronunciation, Phonetics, and Playbook’ is an e-book for children of ages 10 to 12 years old, written in the form of a short story about one of the most famous Malaysian folktale characters, Sang Kancil, The Clever Mouse-deer. The purpose of this educational e-book is to help children pronounce English words correctly at a young age. Educators today are leaning towards a more modernised teaching method in using digital forms of teaching materials; hence, this e-book is ideal to be used by teachers in teaching English pronunciations. Equipped with exercises, learners not only practise their pronunciation by reading, but their pronunciation skill is further enhanced through completing these exercises. The method of completing this e-book includes doing some research on local and international children's phonetic books, writing a short story for the chosen folktale, proofreading and editing, exploring suitable platforms to create the e-book, illustrating and designing the e-book, and finalising the product. It is hoped that this e-book will gain recognition and subsequently be turned into a series of children phonetic and phonology books featuring more Malaysian folktales.